Hydrocarbon and heavy metal pollution of water and sediments of Cross River and Akwa Ibom coastal waters, Nigeira (2005)
A study was undertaken to determine the total hydrocarbon (THC) and heavy metal content of water (surface: 0-15 cm and bottom: 2-13m), sediments (intertidal and waterbed) in coastal area of Cross River and Akwa Ibom states of Nigeria affected by a major oil spill in 1998. Water and sediments samples were collected in the dry (March and December) and wet (July and October) seasons between 1999 and 2002. Significant spatial variation (p-<0.05) was observed for THC and heavy metals. THC (mg/ L) averaged 0.998 for surface and 0.827 for bottom water. All heavy metals of interest: chromium, copper, cadmium, lead, iron, manganese, zinc, and vanadium were present in samples and sediments contained significantly higher (0.05) THC and heavy metals than water. Concentrations of THC in water and sediments exceeded World Health Organization's limits by an average of 0.9979 and 0.8269mg/L in surface and bottom waters respectively.